IMPLEMENTATION OF PRODUCTION MANAGEMENT IN AN EFFORT TO INCREASE MSME INCOME (NASHA PRODUCT BALIKPAPAN) - Mahfudnurnajamuddin; Nur Alam; Andi Muhammad Adib Asharil (Journal Informatic, Education and Management (JIEM), 2026)
Production management is the process of making decisions efficiently and effectively. The purpose of this study is to examine the implementation of four management functions in the Nasha Product MSME, which has significant potential for continued growth. Data collection techniques were conducted through direct interviews with the business owner and observations through social media. The analysis technique used was descriptive analysis. The results of the study indicate that the four management functions of planning, organizing, directing, and controlling have been implemented by the Nasha Product MSME, however, the organizing and controlling functions have not been implemented optimally